Bibliometric Analysis: Trends Research in Junior High School Natural Science Learning Based on Local Potential in 2021-2024 - Putri, Anggraita Febriana; Artanto, Dicky (Proceeding International Conference on Religion, Science and Education, 2025)
Bibliometric analysis can describe various kinds of relevant information about natural science learning in junior high school which is implemented based on local potential. The purpose of this study is to analyze literature on science learning in junior high school based on local potential using bibliometric analysis methods. Data collection techniques are carried out through the Harzing’s Publish or Perish (PoP) application which is linked to the Google Scholar page. The search was carried out to obtain Indonesian-language articles published between 2021 and 2024 through three keywords, namely "Natural Science", "Junior High School", and "Local Potential". The data that has been obtained is then analyzed using VOSviewer to obtain a visualization of research trends. Based on the results of the study, it was found that natural science learning that is collaborated with local potential can have a positive influence on the learning and teaching process. The research map obtained shows a focus on the development and implementation of learning models, learning approaches, teaching materials, learning media, and management of science learning curriculum based on local regional potential. This research is expected to provide broader references regarding the development of science learning research as well as recommendations for education practitioners and researchers